Process optimization and flavor characteristics of cream cheese fermented with avocado co-cultures - Feng Zhang; Yaling Gu; Yuwei Guo; Muhammad Aaqil; Xiaolin Huang; Jingchuan Zheng; Zekun Shi; Yang Tian; Li Zhuang; Cunchao Zhao (Food Chemistry: X, 2025)
This study investigated the impact of avocado co-fermentation on the texture, microstructure, and flavor profile of cream cheese. Avocado puree served as an substrate for R704, yielding a viable cell count of 187.67 × 106 CFU/g after fermentation. All five starter cultures reduced leathery and earthy notes, with R704 showing the most pronounced improvement. In avocado cream cheese 1 (ACC1), protein and fat aggregates were densely packed. ACC2 exhibited a uniform protein–fat distribution, whereas ACC3 showed whey separation. Headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) revealed that ACC1 had a complex aroma profile characterized by floral, fruity, and cheesy notes, as well as a pungent odor. ACC3 exhibited creamy and fruity aromas, yet was accompanied by rancid and bitter undertones. In contrast, ACC2 presented a dominant fruity aroma, minimal off-flavor compounds, and a well-balanced flavor profile. This study provides theoretical support for the development of fermented dairy products incorporating plant-derived lipids.